Microbial Communities in the Extraradicular and Intraradicular Infections Associated With Persistent Apical Periodontitis - Sun, Xiaoqiang; Yang, Zi; Nie, Yong; Hou, Benxiang (Frontiers in Cellular and Infection Microbiology, 2022)
Microorganisms in the complex root canal system and the extraradicular regions, including the periapical lesions and extraradicular biofilm may cause root canal treatment failures. However, few studies described the difference between the intraradicular and extraradicular infections from the same tooth associated with persistent apical periodontitis. This study aimed to characterize the microbiome present in the root canal, extraradicular biofilm, and periapical lesions associated with persistent apical periodontitis. The microbial communities in the root canal, extraradicular biofilm, and periapical lesions were investigated by Illumina high-throughput sequencing using Illumina Hiseq 2500 platform. The dominant phyla in the extraradicular and intraradicular infections associated with persistent apical periodontitis were Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria, and the genera Fusobacterium, Morganella, Porphyromonas, Streptococcus, and Bifidobacterium dominated across all samples. Although extraradicular infection sites showed higher OTU richness and β-diversity compared to intraradicular samples, the occurrence of sinus tract rather than the sampling sites demarcated the microbial communities in the infections associated with persistent apical periodontitis. PERMANOVA analysis confirmed that the samples with or without sinus tracts contained significantly different microbial communities. Porphyromonas, Eubacterium, Treponema, and Phocaeicola were found in significantly higher levels with sinus tracts, whilst Microbacterium and Enterococcus were more abundant in samples without sinus tracts. In conclusion, diverse bacteria were detected in both intraradicular and extraradicular infections associated with persistent apical periodontitis, which might be influenced by the occurrence of the sinus tract. The results may provide new insight into the pathogenesis of persistent apical periodontitis.